Eyes Don’t Lie: Student Evaluation of Teachers Using Participant Facial Expressions - Scott Frasard (Adult Education Research Conference, 2013)
Organizations’ training departments must continue to find ways to demonstrate their contribution. Very frequently, this is accomplished with satisfaction surveys. While only one piece of the effectiveness puzzle, it is affected by response rates and data accuracy. A potential solution to both challenges may lie in a measure of learners’ emotional state as a proxy for satisfaction.